Preparative Fractionation of Phenolic Compounds and Isolation of an Enriched Flavonol Fraction from Winemaking Industry By-Products by High-Performance Counter-Current Chromatography - Fontana, Ariel Ramón (2023)
High-performance counter-current chromatography (HPCCC) was used as a tool for the isolation and fractionation of phenolic compounds (PCs) in extracts from wine lees (WL) and grape pomace (GP). The biphasic solvent systems applied for HPCCC separation were n-butanol:methyl tert-butyl ether:acetonitrile:water (3:1:1:5) with 0.1% trifluoroacetic acid (TFA) and n-hexane:ethyl acetate:methanol:water (1:5:1:5). After refining the ethanol:water extracts of GP and WL by-products by ethyl acetate extraction, the latter system yielded an enriched fraction of the minor family of flavonols. Recoveries of 112.9 and 105.9 mg of purified flavonols (myricetin, quercetin, isorhamnetin, and kaempferol) in GP and WL, respectively, from 500 mg of ethyl acetate extract (equivalent to 10 g of by-product) were obtained. The HPCCC fractionation and concentration capabilities were also exploited for the characterization and tentative identification of constitutive PCs by ultra-high performance liquid chromatography-mass spectrometry (UHPLC-MS). In addition to the isolation of the enriched flavonol fraction, a total of 57 PCs in both matrixes were identified, 12 of which were reported for the first time in WL and/or GP. The application of HPCCC to GP and WL extracts may be a powerful approach to isolate large amounts of minor PCs. The composition of the isolated fraction demonstrated quantitative differences in the individual compound composition of GP and WL, supporting the potential exploitation of these matrixes as sources of specific flavonols for technological applications.